A model of assessment the effectiveness of innovative growth of Kazakhstan’s human resources - Sung-Kyu Lee, Sung-Kyu Lee; Ramashova, A.N. (BUKETOV BUSINESS REVIEW, 2018)
The article considers and suggests a scheme of an integrated approach to the processes of formation and development of innovation-oriented human resources. The authors developed a model for assessing the effectiveness of using innovative growth in human resources in the Republic of Kazakhstan. The authors identified a set of interrelated economic and mathematical models. At the same time, a methodology has been developed for calculating the valuation of innovation-oriented human resources. The authors calculated the current investments in the activation of innovative development of human resources as the processes of innovation development improve and improve on the basis of the quality of human resources. The complex and a number of economic and mathematical models have been identified, on the basis of which it is possible to forecast the volume of production of innovative products, depending on the dynamics of investment changes and innovation-oriented personnel potential in the manufacturing industry. At the same time, a methodology has been developed for calculating the valuation of innovation-oriented human resources on the basis of a special coefficient (goodwill) to the cost of traditional labor, taking into account the cost of knowledge and skills. A two-level complex of models is finally formed. The main payback period for production has been determined. The main motives are deducing the estimates of the economic efficiency of human resources as an innovative factor in the development of the economy.